Analysis Of Giving Fast Food With Nutritional Status In Pre-School Children In Ra Al−Hidayah Tarik Village Tarik Sidoarjo District Year 2020 - Kuryati,; Risna Zubaidah,; Donny Irawan, (Journal of Health Science Community, 2023)
One of the causes of and higher nutritional status of children under five is the frequent consumption of fast food. The habit of giving ready-to-eat food is probably due to the mother's ignorance of the dangers of ready-to-eat food and its implications for the nutritional status of pre-school children and lifestyle factors. The purpose of this study was to analyze ready-to-eat food with nutritional status in school-age children in Al-Hidayah kids park, Tarik Village, Tarik Sidoarjo District 2020. The method used is correlational analytic with cross sectional approach. The population is all mothers of pre-school age children in RA Al-Hidayah, Tarik Village, Tarik District, Sidoarjo Regency with a sample size of 47 respondents. The sampling technique is simple random sampling. The research instrument used a questionnaire. The results showed the Spearman Rank value is 0,000 which means there is a relationship between x and y because <0.05 Figures are free from positive values ​​of -0.503, so it can be said the relationship between the two variables is not unidirectional. Thus it can be interpreted that the more often prepared fast food the more nutritional status. From the output above -0,503 it can be rejected that the relationship between the provision of ready-to-eat food and nutritional status is sufficient.The solution needed is information assistance delivered by health workers about ready-to-eat food and its implications for the nutritional status of pre-school children.